COST OF POOR LEADERSHIP - Kumar, Ramesh (Digital Repository of Theses - SSBM Geneva, 2022)
Leadership is not for everyone. Before you make anyone a leader the first and foremost question that needs to be asked is if the person is passionate, capable and has an intrinsic desire to inspire others to become great and do great things for the organization. A wrong decision at this stage goes on to impact the organization in loss of revenue, customers, employee engagement and profitability. Most people understand that subpar leaders/managers have a negative impact on the organization. However, when you look at how big the cost of poor leadership really is, then you begin to re-examine the importance of leadership within the company. Poor leadership is undoubtedly one of the main potential factor that can lead an organization to failure . A consistently successful business is more likely to have capable leaders who are able to steer the organization towards the desired goals, vision and mission. Leaders influence a variety of outcomes such as customer satisfaction, sales, revenue, productivity, employee satisfaction and employee retention. Conversely, poor leadership can have a negative impact on all the above, lack of growth in business can also have further impact to economy, loss of jobs and livelihood. Poor leadership can be defined as leadership style, intents, actions that are pushing an organization away from realizing the organizations goals, mission and vision. Bad managers cost businesses billions of dollars each year and having too many of them can bring down a company. The only defense against this problem is a good offense, because when companies get these decisions wrong, nothing fixes it. Leadership development is an area which has the potential but is not able to solve the crisis of poor leadership in most organizations. Leadership development programs do not yield immediate results, there is a lack of credible leadership development programs, 4 there is no time and effort factored in for developing leaders. This results in substandard leaders across the leadership hierarchy of the organization. Finally, an important aspect in this cycle is lack of contribution from academia. Schools and colleges do not have a concept of imbibing leadership skills and traits in students as part of their graduation curriculum, this means that organizations and business have the task of identifying first time managers in an environment where all entry level employees are only technically qualified and do not possess any leadership skills. Through a combination of research, studies and qualitive surveys, this research attempts to address Cost Of Poor Leadership and provides a solution framework for resolution and for creating a steady pipeline of successful business leaders.